Genealogi Konflik Etnis Dayak dan Madura Di Kalimantan Barat - Agus Darmaji; M. Amin Nurdin; Muhammad Hafiy bin Abd Razak (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
Conflict is a persistent social phenomenon in human life, often triggered by social change, differences in authority, interests, and culture. As a nation with high ethnic diversity, Indonesia is particularly vulnerable to ethnic conflict. This article aims to explore the genealogy of ethnic conflicts and propose alternative resolutions through a case study of the conflict between the Dayak and Madurese ethnic groups in West Kalimantan. The research employs documentation methods and Focus Group Discussions (FGDs) to gather data from relevant institutions, researchers, intellectuals, and conflict survivors. The findings reveal that conflicts are often sparked by personal incidents, yet their escalation is influenced by social, cultural, economic, and political factors. The limited role of the government in addressing these conflicts is identified as one of the main barriers to resolution. This article recommends multiculturalism-based resolution approaches and cross-cultural dialogue as efforts to build harmonious relationships between ethnic groups.